Transient Glyco-Engineering to Produce Recombinant IgA1 with Defined N- and O-Glycans in Plants - Dicker, Martina; Tschofen, Marc; Maresch, Daniel; König, Julia; Juarez, Paloma; Orzaez, Diego; Altmann, Friedrich; Steinkellner, Herta; Strasser, Richard (Frontiers in Plant Science, 2016)
The production of therapeutic antibodies to combat pathogens and treat diseases, such as cancer is of great interest for the biotechnology industry. The recent development of plant-based expression systems has demonstrated that plants are well-suited for the production of recombinant monoclonal antibodies with defined glycosylation. Compared to immunoglobulin G (IgG), less effort has been undertaken to express immunoglobulin A (IgA), which is the most prevalent antibody class at mucosal sites and a promising candidate for novel recombinant biopharmaceuticals with enhanced anti-tumor activity. Here, we transiently expressed recombinant human IgA1 against the VP8* rotavirus antigen in glyco-engineered ΔXT/FT Nicotiana benthamiana plants. Mass spectrometric analysis of IgA1 glycopeptides revealed the presence of complex biantennary N-glycans with terminal N-acetylglucosamine present on the N-glycosylation site of the CH2 domain in the IgA1 alpha chain. Analysis of the peptide carrying nine potential O-glycosylation sites in the IgA1 alpha chain hinge region showed the presence of plant-specific modifications including hydroxyproline formation and the attachment of pentoses. By co-expression of enzymes required for initiation and elongation of human O-glycosylation it was possible to generate disialylated mucin-type core 1 O-glycans on plant-produced IgA1. Our data demonstrate that ΔXT/FT N. benthamiana plants can be engineered toward the production of recombinant IgA1 with defined human-type N- and O-linked glycans.